The special case of disadvantaged young people in Germany : how stakeholder interests hinder reform proposals in favour of a training guarantee - Granato, Mona [Verfasser]; Krekel, Elisabeth M. [Verfasser]; Ulrich, Joachim Gerd [Verfasser] (My University, 2015)
"Every year, tens of thousands of young people in Germany fail to find access to dual vocational education and training (VET), because they cannot find a company to hire them as apprentices. This particularly affects persons with poor school leaving qualifications, socially deprived persons or people with a migrant background. In order to improve their opportunities, there has been an increased discussion in recent times about a training guarantee. The central idea is that unsuccessful applicants undergo training at extra-company training institutions. This paper investigates the chances of realising such a reform proposal on the basis of organisational theories like agency theory and neo-institutionalism. The assumption is that particularly stakeholders from the employers' and business associations will have reservations. Since their power within the state-corporatist governance system of dual VET seems to be higher than the power of the trade unions, the chances for this reform proposal should be relatively low. A survey of 300 stakeholders from different organisations that are involved with the governance, administration, implementation of and research into VET confirms this assumption. Apparently, disadvantaged young people are still expected to adapt to the less attractive residue of company-based training offers that are not taken up by better qualified applicants." (Authors' abstract, BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; P 1.7 Benachteiligte; P 1.1 Jugendliche; G 1.3.2.2.1 Erste Schwelle, in Ausbildung; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; S 4.3 Steuerung; T 4.5 Soziologie; Berufsausbildung; Duales System; Benachteiligter Jugendlicher; Ausbildungsbeteiligung; Bildungsreform; Berufseinmündung; Erste Schwelle; Ausbildungschance; Ausbildungsgarantie; Bildungssteuerung; Korporatismus